2001
DOI: 10.1046/j.1528-1157.2001.37500.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizure‐Associated Headache in Epilepsy

Abstract: Summary:Purpose: Headache is often ignored as a symptom of epileptic seizures. The purpose of this prospective study was to analyze frequency, classification, and characteristics of seizure-associated headache (SH) according to the criteria of the International Headache Society.Methods: Over a period of 15 months, 341 patients with epilepsy, consecutively evaluated at our outpatient clinic for SH, completed a standardized questionnaire.Results: Of the 341 epilepsy patients, 115 (34%) experienced SH with a pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
73
5
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 18 publications
15
73
5
2
Order By: Relevance
“…Yankovsky et al found 48% [12]. In a study by Leniger et al, 56% of peri-ictal headache was classified as migraine [16], while Förderreuther et al reported 34% [7]. These findings are in accordance with our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Yankovsky et al found 48% [12]. In a study by Leniger et al, 56% of peri-ictal headache was classified as migraine [16], while Förderreuther et al reported 34% [7]. These findings are in accordance with our study.…”
Section: Discussionsupporting
confidence: 92%
“…Many authors have tried to explore this association, but with rather diverse findings. The prevalence of migraine in individuals with epilepsy varies from 2% to 24% [4,6,7,11,12,[16][17][18][19][20]. This large variation is probably due to differences in classifications of both disorders, as well as in the selection of patient populations and diagnostic instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are close to the prevalence of 5-15% for pre-ictal headache that was reported in epilepsy and of especially 11% in pharmacologically refractory partial epilepsy (29)(30)(31). Similar to our findings, in the other studies, post-ictal headaches are more common than pre-ictal headaches which are often the migraine type and especially occur after some types of epilepsy such as generalized tonic-clonic and occipital lobe epilepsies (1,29,32,33). Limitations of this study were small sample size, prospective nature of the study and undifferentiated epileptic syndromes.…”
Section: Discussionsupporting
confidence: 91%
“…Obviously, additional (antinociceptive) properties of TGB and GBP, administered in combinations, could ameliorate the patients' quality of living, especially those, who similar to healthy people, suffer from various pain disorders that are or not related with epilepsy, for instance: headaches, algomenorrhoea, etc. (Savoldi et al, 1984;Leniger et al, 2001;Nair et al, 2001). Due to this additional antinociceptive component, combinations of TGB with GBP might become much more efficacious from a clinical point of view.…”
Section: Controlmentioning
confidence: 99%